Psychological treatments of the irritable bowel syndrome: a review. Issue 11 (November 1989) - Creed, F; Guthrie, E
Abstract : Psychological treatments are increasingly being used to help patients with the irritable bowel syndrome (IBS), but the efficacy of such treatments is still debated. This review indicates that there are three ways in which they might have been effective in published studies to date; relating bowel symptoms to stress, specific help with psychosocial problems/relationships and relaxation to decrease anxiety and tension. A close doctor-patient relationship is regarded as central to these therapeutic tasks but the time required to maximise the effectiveness of this therapeutic role means that intensive psychological treatment should be reserved for those IBS patients who do not respond to first line standard medical treatment. There are insufficient data to indicate at present which patients are best suited to each form of psychological treatment.